Socio-demographic characteristics of caregivers and the clinical profile of undernourished under five year old children admitted in Nyangabgwe Referral Hospital, Botswana - Madondo, Andrew (University of Limpopo (Medunsa Campus), 2012)
Background: Despite Botswana being a middle income country undernutrition among children younger than five years of age continues to affect different parts of the country. Undernutrition can be attributed to a number of reasons which vary from region to region. There is little information on the socio-demographic characteristics of caregivers and the clinical profile of undernourished children in Francistown and surrounding villages. Purpose: To determine the socio-demographic characteristics of caregivers and the clinical profile of undernourished children admitted at Nyangabgwe Referral Hospital, Francistown, Botswana. Method: Data were collected from 113 caregiver-child pairs using a researcher administered questionnaire targeting caregivers and the child's hospital card and the child's anthropometric measurements were taken. Data were analysed using the WHO Anthro 2006 software and Stata 10. Descriptive statistics were derived and Chi -square tests were done at 5% level of significance to determine any associations. Results: The majority of the caregivers were single mothers (80%) younger than 30 years of age. Oedematous malnutrition was found in 50% of the children and was more common in males at 55%. The reasons given by caregivers as to why their children had been admitted did not relate to the child's nutritional state. The child's gender was associated with stunting (X2 = 4.0638, P = 0.044) at 5% level of significance. Looking at any associations between caregiver characteristics and the child's clinical profile only marital status was associated with child presenting with cough (X2 = 4.0947, P = 0.045) at 5% level of significance. There was no association between the caregiver characteristics and the severity of any of the three types of undernutrition (wasting, stunting and underweight). Conclusion: This study showed that the majority of caregivers were younger than 30 years of age and single. The child's gender was associated with stunting which may need more research on. Almost 50% of the children had oedematous malnutrition. Public health interventions should focus on providing caregivers with health education on the early signs of undernutrition so as to facilitate timely interventions and prevent severe cases of undernutrition.
Thesis (MPH) -- University of Limpopo, 2012.
Keywords: Caregivers